The Effect of Principal Leadership Style and Work Motivation on Elementary Teacher Performance: A Study in Public Schools of Gunung Kerinci District - Nemi Setrianti; Sumanti Sumanti; Siti Aisyah (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
Effective school management relies heavily on the principal's leadership qualities and teachers' levels of work motivation, both of which are considered major determinants of teacher performance. This study aims to examine the influence of principals' leadership style and work motivation on classroom teachers' performance in State Elementary Schools in Gunung Tujuh District, Kerinci Regency. A quantitative explanatory research design was used, involving all 87 classroom teachers in public elementary schools in the sub-district as the research population, using the census method. Data were collected using a validated questionnaire instrument with a five-point Likert scale and analyzed using multiple linear regression. The results showed that the principal's leadership style had a positive and significant effect on teacher performance (β = 0.412; p < 0.001), work motivation had a positive and significant effect on teacher performance (β = 0.378; p < 0.001), and the two variables together had a significant effect on teacher performance with a value of R² = 0.623, which means that 62.3% of the variation in teacher performance was explained by these two variables. These findings emphasize the importance of adaptive transformational leadership and sustained motivational support in enhancing classroom teachers' professional effectiveness in rural primary schools.